Visualization of firm linkages in the Chicago ICT cluster. Issue 1 (1st January 2018) - Byrne, Eoin; Hobbs, John; Doran, Justin
Abstract: Do industry clusters derive their success from a strong 'local buzz' or from access to 'global pipelines'? This important question is addressed in the context of the Chicago (Illinois, United States) information and communication technology (ICT) cluster, which has shown growth and dynamism and is a significant sector not only in terms of the jobs it creates directly but also by supporting other sectors in Chicago. Cluster mapping and analysis studies have provided industry and policy-makers with instruments to explain the cluster structure and its connection to an economy for over two decades. Visualization of linkages in networks and clusters (V-LINC), a methodology that records, maps and analyses the linkages that firms in clusters engage in, is applied to the ICT sector in Chicago. Visualizing the firm linkages of Chicago ICT firms provides a geographical footprint of the cluster's ecosystem. Through an understanding of the various linkages that firms in a cluster engage in, targeted policy recommendations can be developed to build on strengths and address weaknesses. The visualization of firm linkages has considerable potential to add to cluster analysis by improving how data are portrayed, the dissemination of research and explaining how clusters operate.